Future mortality in low-mortality countries - Graziella Caselli; Sven Drefahl; Marc Luy; Christian Wegner-Siegmundt; Michel Guillot; France Meslé; Arodys Robles; Richard G. Rogers; Edward Jow-ching Tu; Zhongwei Zhao (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2013)
4802 This paper provides an overview of past and expected future trends in life expectancy in populations of today's low mortality countries. Because these populations previously experienced strong decreases in infant mortality, the future mortality trends will be driven mainly by mortality among the old and oldest-old. The paper gathers empirical background data and theoretical considerations about past and likely future determinants of mortality including smoking, obesity, biomedical progress, environmental changes and socioeconomic conditions. Based on this knowledge an internet expert survey and a meta-experts meeting were carried out to formulate expert-based assumptions for future trends in life expectancy. The presented evidence and the experts' assessments indicate that that the positive influences on human mortality and life expectancy will likely outweigh the negative risk factors and lead to further increases of life expectancy. Moreover, the paper concludes that the differences between countries are likely to narrow further in the future.
Keywords: 300; mortality; life expectancy; determinants; future; trends; low mortality countries; projection